THE CONSTITUTIONALITY OF INTERFAITH MARRIAGE IN INDONESIA: HARMONIZING ISLAMIC LAW AND HUMAN RIGHTS FROM A PROGRESSIVE FIQHI PERSPECTIVE - Aswidia Agustin; Fera Zabira Zahra; Risdawati Syam; Andi Muhammad Akmal (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin Makassar, 2024)
ABSTRACT Interfaith marriage in Indonesia raises polemics between Islamic law and Human Rights (HR), especially in terms of constitutionality. This study examines interfaith marriage issues from the perspective of Islamic law and HR, aiming to harmonize both. The study employs library research methods with a normative-juridical theory approach, HR, progressive law, and progressive fiqh. Data were collected from primary sources of Islamic law and HR provisions, as well as relevant secondary literature. The findings indicate that interfaith marriage is not an absolute violation under Islamic law; 1) Interfaith marriage in Indonesia is deemed unconstitutional under positive law; 2) Discourse on interfaith marriage between Islamic law and HR garners pro and con views from various contemporary scholars; and 3) Legal harmonization allowing interfaith marriage with court approval in emergency circumstances is needed. The study implies the necessity for policies that respect individual freedom without neglecting constitutional and religious law aspects, fostering a balance between HR and Islamic law in Indonesia. Keywords: Interfaith Marriage; Human Rights; Islamic Law; Progressive Fiqh.